Effects of equid herpesvirus 1 (EHV-1) AR8 and HH1 strains on BALB-c mice - Zanuzzi, Carolina Natalia (2014)
Here, we used a murine model to describe and compare the pathogenic potential of the Argentinean equid herpesvirus 1 (EHV-1) AR8 strain with the Japanese HH1 reference strain. In AR8-inoculated animals, clinical signs began earlier, but the viremic phase was shorter. Virus isolation and DNA detection in the lungs, liver and spleen were positive for both strains at different times postinfection (pi). Infection foci produced by both strains were immunohistochemically detected in lungs from day 1 to day 4 pi. We conclude that whichever EHV-1 strain is selected to experimentally reproduce the disease, it needs appropriate standardization in order to provide valid conclusions.